2006
DOI: 10.1089/jmf.2006.9.552
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Essential Oil Composition and Antifungal Effect of Bitter Fennel (Foeniculum vulgaressp.piperitum) Fruit Oils Obtained During Different Vegetation

Abstract: The chemical composition of the flower and unripe and ripe fruits from fennel (bitter) (Foeniculum vulgare ssp. piperitum) has been examined by gas chromatography and gas chromatography-mass spectrometry. The main identified components of the flower and unripe and ripe fruit oils were estragole (53.08%, 56.11%, and 61.08%), fenchone (13.53%, 19.18%, and 23.46%), and alpha-phellandrene (5.77%, 3.30%, and 0.72%), respectively. Minor qualitative and major quantitative variations for some compounds of essential oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 23 publications
2
76
0
Order By: Relevance
“…Recently there has been considerable emphasis on studies involving effects of aromatic plants and extracts of herbs on inhibiting the growth of microbes [Ozcan et al, 2006]. Spoilage of bakery products is caused mainly by moulds and yeasts and occasionally by bacteria such as the rope causing heat-resistant endospore-forming Bacillus subtilis [Ozcan et al, 2006].…”
Section: Effect Of Aromatic Plants On the Microbial Load Of The Piementioning
confidence: 99%
“…Recently there has been considerable emphasis on studies involving effects of aromatic plants and extracts of herbs on inhibiting the growth of microbes [Ozcan et al, 2006]. Spoilage of bakery products is caused mainly by moulds and yeasts and occasionally by bacteria such as the rope causing heat-resistant endospore-forming Bacillus subtilis [Ozcan et al, 2006].…”
Section: Effect Of Aromatic Plants On the Microbial Load Of The Piementioning
confidence: 99%
“…[24] Mimica-Dukic et al [9] also reported trans-anethole (74.18%), fenchone (11.32%), estragole (5.29%), limonene (2.53%) and α-pinene (2.77%) as the major compounds identified in the essential oil from Foeniculum vulgare Mill. Ozcan et al [10] and Ozcan and Chalchat [25] reported estragole (61.08% and 40.49%), fenchone (23.46% and 16.90%) and limonene (8.68% and 17.66%), respectively, as the major constituents in the essential oil of bitter fennel (F. vulgare spp. piperitum) grown in Turkey.…”
Section: Chemical Composition Of the Essential Oilmentioning
confidence: 99%
“…Mimica-Dukic et al [9] also reported that the essential oils of fennel are active against Aspergillus species. Ozcan et al [10] reported the antifungal activity of essential oils from bitter fennel. As expected, fennel seed extracts offered no antimicrobial activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of compounds was done based on the following explanation: the retention indices were calculated for all volatile constituents using a homologous series of n-alkanes C6 to C24. Moreover, the method of mass spectra was used for the identification of individual compounds with those of similar compounds from a database (Wiely/NBS library) or with authentic compounds and it was confirmed by the comparison of their retention indices with authentic compounds or with those reported in the literature (Ozcan et al, 2006). For quantification purpose, relative area percentages obtained by flame ionization detector (FID), were used without using correction factors.…”
Section: Gc-ms Analysis Of Essential Oilmentioning
confidence: 99%